URBAN HEAT ISLANDS AND THERMAL COMFORT IN CDHU RESIDENCES DURING SPRING EPISODES IN MARTINÓPOLIS/SP - Milani, Tiago Santos [UNESP]; Amorim, Margarete Cristiane de Costa Trindade [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2024)
The Companhia de Desenvolvimento Habitacional Urbano do Estado S & atilde;o Paulo (CDHU) was a key housing policy initiative by the State Government. Aimed at addressing the growing housing deficit throughout the 20th century, the company prioritised mass construction of houses, often overlooking local climatic realities and resulting in high construction density. The business model exhibited characteristics that foster the emergence of heat islands, compromised thermal comfort for residents, and pottencially leading to precarious living conditions and health issues. Drawing on the theoretical and methodological framework of the Urban Climate System (MONTEIRO, 1976), this paper investigates the manifestation of heat islands and their correlation with indoor and outdoor thermal comfort in CDHU homes in the city of Martin & oacute;polis, S & atilde;o Paulo (SP), using the Temperature-Humidity Index (THI) (THOM, 1959). The findings indicate that heat islands of strong or very strong magnitude impact the external thermal comfort of the houses, while the internal thermal comfort tends not to demonstrate this relationship.
Keywords: Urban Climate; Heat islands; Thermal Comfort